Usulan Pengendalian Tingkat Persediaan Bahan Baku dengan Metode Economic Order Quantity di PT XYZ - M. Dhiemas Agung Kurnia; Agustian Suseno (Fakultas Teknik, 2023)
Stock is the most unique and significant working capital in an organization that has material value. Material stock control needs to be considered because it is directly related to the costs that must be borne by the organization. Companies must carry out inventory control to determine the optimal amount of inventory levels needed and when to buy or reorder goods. An inventory management strategy called EOQ takes carrying and ordering costs into account. It is assumed that demand quantities are known, lead times are known and constant, and stock shortages can be completely avoided by placing orders on time. The EOQ method is often used because it is easy to implement and can provide the best solutions for businesses. The Economic Order Quantity (EOQ) method which is based on the inventory model formula produces an economical order quantity, 670, which results in reduced ordering and holding costs to minimize PT XYZ and maximize profits. PT. XYZ should be able to determine the amount of safety stock, reorder point as an effort to avoid the risk of running out of raw materials and excess of raw materials so as to reduce the costs required to purchase raw materials.